2004
DOI: 10.1210/jc.2003-032208
|View full text |Cite
|
Sign up to set email alerts
|

3,5,3′-Triiodothyronine Down-Regulates Fas and Fas Ligand Expression and Suppresses Caspase-3 and Poly (Adenosine 5′-Diphosphate-Ribose) Polymerase Cleavage and Apoptosis in Early Placental Extravillous Trophoblastsin Vitro

Abstract: The present study was conducted to determine whether T(3) receptor exists in early placental extravillous trophoblasts (EVTs) and evaluate the influence of T(3) on Fas/Fas ligand expression, caspase-3, and poly (ADP-ribose) polymerase (PARP) cleavage and apoptosis in cultured early placental EVTs. EVTs with invasive phenotype, isolated from normal placental explants from early pregnancy through preincubation on human fibronectin-coated dishes and exhibited cytokeratin 7 and human placental lactogen immunoposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 75 publications
4
33
0
Order By: Relevance
“…Although THs are known to exert many of their effects via classical regulation of gene transcription, a large number of their actions occur rapidly and are unaffected by inhibitors of transcription and protein synthesis (Yen 2001, Davis & Davis 2002, Incerpi 2005. Analyzing available data indicated that thyroid status influences sensitivity to apoptosis (Lin et al 1999, Qi et al 1999, Antonelli et al 2004, Laoag-Fernandez et al 2004, Verga Falzacappa et al 2006, we questioned whether T 3 -activated signaling could suppress DRLs-induced apoptosis. In this study, we found that THs counteract apoptotic effects of Fas/TNF and prevent hepatocyte apoptosis in a rapid non-genomic manner independent of transcriptional activity (Figs 1 and 2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although THs are known to exert many of their effects via classical regulation of gene transcription, a large number of their actions occur rapidly and are unaffected by inhibitors of transcription and protein synthesis (Yen 2001, Davis & Davis 2002, Incerpi 2005. Analyzing available data indicated that thyroid status influences sensitivity to apoptosis (Lin et al 1999, Qi et al 1999, Antonelli et al 2004, Laoag-Fernandez et al 2004, Verga Falzacappa et al 2006, we questioned whether T 3 -activated signaling could suppress DRLs-induced apoptosis. In this study, we found that THs counteract apoptotic effects of Fas/TNF and prevent hepatocyte apoptosis in a rapid non-genomic manner independent of transcriptional activity (Figs 1 and 2).…”
Section: Discussionmentioning
confidence: 96%
“…It is important that most of plasma membrane and cytosol targets of THs have been strongly circumstantially linked to mitogenic and antiapoptotic signaling pathways (Qi et al 1999, Laoag-Fernandez et al 2004, Verga Falzacappa et al 2006. For instance, THs were able to activate the Na C /H C exchanger (NHE) and reduce intracellular acidity produced by activated sodium currents in different cells (Wang et al 2003, D'Arezzo et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Both T3 and T4 stimulate EGF production by primary cytotrophoblasts, in turn 320 enhancing their survival [11]. In primary EVTs, T3 has been shown to suppress apoptosis [43] and promote invasion [12], whilst in an EVT-like cell line, T3 in conjunction with EGF, suppresses proliferation and increases cell motility [10]. The expression of MCT8, MCT10 and OATP1A2 in both cytotrophoblasts and EVTs during the 1 st trimester of pregnancy could allow TH cellular uptake into target cells and thus mediate TH action during early 325 placental development.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not T 3 also enhances thymocyte survival has not been determined. Yet, this hypothesis deserves investigation in view of the data showing that T 3 promotes a decrease in the expression of Fas and Fas ligand in cultured human trophoblastic cells, simultaneously with a suppression of apoptosis and reduced caspase-3 expression [52].…”
Section: Discussionmentioning
confidence: 99%